Validation and adaptation of the diffusion of intimate images among adolescents (EDIMA) scale in adolescents from Peru - Figueroa-Quiñones, Joel; Ipanaqué-Zapata, Miguel; Rivera-Lozada, Oriana; Villalobos-Quiroz, Cecilia Gabriela; Vilcabana-Burgos, Axel Glynda; Valle-Chafloque, Ibeth Solange (Frontiers in Psychology, 2024)
The use of technologies through social networks is a common practice among adolescents who use it to communicate. However, the lack of control and supervision of these media means that they disseminate any type of information, including sexual content. OBJECTIVE: to evaluate the psychometric properties of the Intimate Images Diffusion Scale (EDIMA) in Peruvian adolescents. METHOD: A psychometric study was conducted with a population of 900 adolescents from the coast, highlands and jungle of Peru. A confirmatory factor analysis and measurement invariance analysis was performed by age and sex groups. In addition, internal consistency was evaluated through the omega index to estimate the reliability of the scale. RESULTS: Our study identified that the two-factor model obtained adequate fit indices with values > 0.994 for the CFI and TLI, while the SRMR had a value of 0.074 and the RMSEA of 0.058. Measurement invariance by age group reported a ΔCFI and ΔRMSEA ≤ 0.01. Reliability reported a McDonald's ω greater than 0.8 CONCLUSIONS: The EDIMA is a valid and reliable instrument to evaluate the dissemination of intimate images among adolescents from various regions of Peru.